MMS observations of large guide field symmetric reconnection between colliding reconnection jets at the center of a magnetic flux rope at the magnetopause. Issue 11 (4th June 2016) - Øieroset, M.; Phan, T. D.; Haggerty, C.; Shay, M. A.; Eastwood, J. P.; Gershman, D. J.; Drake, J. F.; Fujimoto, M.; Ergun, R. E.; Mozer, F. S.; Oka, M.; Torbert, R. B.; et al.
Abstract: We report evidence for reconnection between colliding reconnection jets in a compressed current sheet at the center of a magnetic flux rope at Earth's magnetopause. The reconnection involved nearly symmetric inflow boundary conditions with a strong guide field of two. The thin (2.5 ion‐skin depth ( di ) width) current sheet (at 12 di downstream of the X line) was well resolved by MMS, which revealed large asymmetries in plasma and field structures in the exhaust. Ion perpendicular heating, electron parallel heating, and density compression occurred on one side of the exhaust, while ion parallel heating and density depression were shifted to the other side. The normal electric field and double out‐of‐plane (bifurcated) currents spanned almost the entire exhaust. These observations are in good agreement with a kinetic simulation for similar boundary conditions, demonstrating in new detail that the structure of large guide field symmetric reconnection is distinctly different from antiparallel reconnection. Key Points: First report of magnetic reconnection in a compressed thin current sheet between colliding jets at the center of a magnetic flux rope Large guide field causes asymmetries in plasma and field structures in the reconnection layer Excellent agreement in plasma and field profiles between observations and 2‐D particle‐in‐cell simulation